A Narrative Review of Ethnic Minority Studies for Faith-Based Health Promotion Interventions with Special Reference to the Contemporary Christian Nurse - Blankinship, Lisa A. (Journal of religion and health, 2021)
Heart disease, diabetes mellitus (DM) type 2, and obesity are three of the most prevalent diseases in the USA. Some obesity-related comorbidities are disproportionately higher within African-American and Hispanic communities. While governmental and local health programs offer educational opportunities encouraging long-term health behavior changes, the most accessible programs have been through faith-based communities. This narrative review investigates the outcomes of faith-based wellness programs on Latino and African-American populations with respect to general health and wellness, obesity management, DM type 2, and hypertension. Perceived authority of faith community nurses, faith leaders, and accountability and encouragement provided by faith communities are critical. Long-term behavior change is positively affected by elements faith-based organizations can provide: cultural appropriateness, community support, and self-efficacy.